(untitled) (Scientific Journal of Research Studies in Future Management, 2025)
In recent decades, Iran’s automotive market has evolved into one of the most complex and competitive in the Middle East. The simultaneous presence of domestic manufacturers and international brands—especially through joint ventures and imports—has created significant challenges in sales, marketing, and consumer behavior analysis. This study aims to conduct a comparative analysis of the sales strategies of three active car manufacturers in the Iranian market: Modiran Khodro, Kerman Motor, and Hyundai. The goal is to assess their respective strengths and weaknesses in adapting to the cultural, economic, and behavioral characteristics of Iranian consumers. The research adopts a mixed-methods approach, combining quantitative data (including sales statistics, pricing models, distribution channels, and advertising strategies) with qualitative insights (such as consumer behavior patterns and customer relationship policies). Data were collected from official statistics, corporate financial reports, academic articles, and market information databases between 2015 and 2024. Findings indicate that foreign brands like Hyundai structure their sales strategies based on precise market segmentation, product diversity, and strong after-sales services. In contrast, although domestic companies benefit from pricing advantages, they exhibit shortcomings in identifying consumer preferences and enhancing the purchasing experience. From the consumer behavior perspective, factors such as economic conditions (e.g., purchasing power and maintenance costs), brand credibility, after-sales services, and cultural elements play key roles in decision-making. The study recommends that domestic automakers adopt more customer-centric policies inspired by successful international models to improve their competitive positioning.